Statistical Learning Ability Influences Adults' Reading of Complex Sentences. - Jared, Debra; Farmaha, Amanda (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2026)
The goal of the present study was to investigate whether a relationship exists between statistical learning ability and sentence processing ability in adult readers and whether this relationship depends on the participant's exposure to print. Fifty participants read syntactically complex sentences while their eye movements were tracked and answered comprehension questions. The region of interest for the eye fixation analyses was the area where the complexity of the sentence became evident. Participants also completed a visual statistical learning (VSL) task and an author recognition test (ART). There were main effects of statistical learning ability and print exposure, as well as an interaction between the two on both first pass and total reading times. Reading times decreased with increasing VSL scores for participants with higher ART scores, whereas reading times increased with increasing VSL scores for participants with lower ART scores. In addition, participants with better statistical learning ability and greater print exposure had higher scores on the comprehension questions. These results demonstrate that efficient processing of complex syntactic structures depends on both good statistical learning skills and exposure to a large amount of print so that these skills have the opportunity to extract the relevant statistical relationships in the language.